Challenging New Targets for CNS–HIV Infection - Ganau, Mario; Prisco, Lara; Pescador, Daniele; Ganau, Laura (Frontiers in Neurology, 2012)
The central nervous system represents an important target for HIV infection during multiple stages of the disease: early, after invasion of the host, acting as a viral reservoir; lately, subverting its function and causing peripheral neuropathies and neurocognitive disorders; and lastly, during the final stage of NeuroAIDS, triggering opportunistic infections, cancers and dementia. Highly active antiretroviral therapy, a combination of drugs that inhibits enzymes essential for HIV replication, can reduce the viremia and the onset of opportunistic infections in most patients and prolong the survival. Among the limits of the current treatments the most noticeable is the inability to eradicate HIV-infected cells, both, limiting the time frame in which antiretroviral therapies initiated after exposure to HIV can prevent infection, and allowing replication-competent virus that persists in infected cells to emerge rapidly after the cessation of treatments. Many strategies are currently under evaluation to improve HIV treatment, unfortunately more than 98% of drug candidates for CNS disorders never make it to the clinic; herein we report how nanoformulated strategies might be adapted and applied to the field of CNS-HIV infection.